2021
DOI: 10.1002/ppap.202100159
|View full text |Cite
|
Sign up to set email alerts
|

A novel two‐dimensional atmospheric pressure plasma jet device

Abstract: A novel two-dimensional atmospheric pressure plasma jet device is proposed for large-area processing. A finite element algorithm is adopted to obtain the optimized dimensions of the designed device based on microwave power reflection coefficient |S 11 | and electric field intensity. The plasma parameters of electron density n e and electron temperature T e within 0.1 ms after microwave power input were analyzed. When plasma is fully excited, n e is close to 3.5 × 10 18 m −3 , and T e is calculated to be 2 eV. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Optimizing the reactor parameter is an important approach to obtain the appropriate dose of RONS in PAW to improve biomedical effects. Motivated by the challenge of using inherently small-scale atmospheric plasma to address large-scale processing applications, a range of discharge devices have been designed in the literature including plasma jet, jet array and other discharge reactors, to produce underwater bubble plasma for realizing high liquid activation efficiency [16][17][18][19][20][21][22]. Cao et al reported a systematic study of spatially extended atmospheric plasma arrays employing many parallel plasma jets packed densely and arranged in a honeycomb configuration [23].…”
Section: Introductionmentioning
confidence: 99%
“…Optimizing the reactor parameter is an important approach to obtain the appropriate dose of RONS in PAW to improve biomedical effects. Motivated by the challenge of using inherently small-scale atmospheric plasma to address large-scale processing applications, a range of discharge devices have been designed in the literature including plasma jet, jet array and other discharge reactors, to produce underwater bubble plasma for realizing high liquid activation efficiency [16][17][18][19][20][21][22]. Cao et al reported a systematic study of spatially extended atmospheric plasma arrays employing many parallel plasma jets packed densely and arranged in a honeycomb configuration [23].…”
Section: Introductionmentioning
confidence: 99%